2012
DOI: 10.1029/2011gb004237
|View full text |Cite
|
Sign up to set email alerts
|

Small ponds with major impact: The relevance of ponds and lakes in permafrost landscapes to carbon dioxide emissions

Abstract: Although ponds make up roughly half of the total area of surface water in permafrost landscapes, their relevance to carbon dioxide emissions on a landscape scale has, to date, remained largely unknown. We have therefore investigated the inflows and outflows of dissolved organic and inorganic carbon from lakes, ponds, and outlets on Samoylov Island, in the Lena Delta of northeastern Siberia in September 2008, together with their carbon dioxide emissions. Outgassing of carbon dioxide (CO2) from these ponds and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(173 citation statements)
references
References 58 publications
(77 reference statements)
7
164
1
1
Order By: Relevance
“…Located between the Arctic Ocean and the Siberian Continent, it also serves as a sentinel for changes within the Lena River catchment area. Finally, this site provides a unique opportunity for the study of small scale processes that are important for large-scale predictions (for example, small ponds have a large impact on the CO 2 balance, Abnizova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Located between the Arctic Ocean and the Siberian Continent, it also serves as a sentinel for changes within the Lena River catchment area. Finally, this site provides a unique opportunity for the study of small scale processes that are important for large-scale predictions (for example, small ponds have a large impact on the CO 2 balance, Abnizova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ponds are generally well mixed and experience high water temperatures during the summer and are, therefore, hotspots for biological activity and CO 2 emission (Abnizova et al, 2012). The ponds in the study area freeze completely in winter, but the timing of freeze-back can vary by up to 2 months depending on the surface energy balance (Langer et al, 2011b).…”
Section: Hydrosphere: Thermal Characteristics Of Ponds and Thermokarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctic ponds are characterized by intense biogeophysical and biogeochemical processes. They have been identified as a large source of carbon fluxes compared to the surrounding terrestrial environment (Rautio et al, 2011;Laurion et al, 2010;Abnizova et al, 2012;Langer et al, 2015;Wik et al, 2016;Bouchard et al, 2015). Due to their small surface areas and shallow depths, ponds are especially prone to change; various studies reported ponds drying out or increasing in abundance due to new thermokarst or the drainage of large lakes (Jones et al, 2011;Andresen and Lougheed, 2015;Liljedahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In many regions, these features maintain the capacity to store and exchange carbon (C) (Macrae et al, 2004;Abnizova et al, 2012), act as a habitat (Smol and Douglas, 2007), and mediate the landscape energy balance (Chapin et al, 2000). These tundra ponds are highly sensitive to climate change (Schindler and Smol, 2006), which may impact their hydrology and biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%